Executive Role in the Use of Information Technology in Public Organisations - Ade Irma Anggraeni (Arthatama: Journal of Business Management and Accounting, 2020)
The use of information technology is a strategic activity on achieving organisational goals. For public organisations, especially government institutions, governance systems, good information not only intended for internal use, but it has a requirement to present information that is accountable to the public quickly. The effectiveness of the use of information technology in organisations is to ensure sustainability of the progressive use of information technology. This study aims to explain the various factors that affect the executive's involvement in the use of progressive information technology in the public sector. The variables of study include executive participation, organisational conditions, background executive, executive involvement and progressive use of information technology. The study was conducted on 295 employees on 23 institutions on Banyumas. The sampling method uses purposive sampling. Data analysis using SPSS and PLS.